RV lead placement – A forgotten cause of right heart failure. (July 2021) - Cheema, Muhammad Arslan; Almas, Talal; Ullah, Waqas; Haas, Donald
Abstract: Introduction: Cardiac implantable electronic devices (CIEDs) have opened new doors, improving the quality, and increasing the duration of life by providing support of heart rate, atrioventricular and interventricular synchrony, thereby preventing sudden cardiac death. Nevertheless, these devices can pose some risks to the patients, including pacemaker-mediated cardiomyopathy and endocarditis. Case presentation: We elucidate the case of a patient who had severe Tricuspid Regurgitation as a result of single chamber Implantable Cardioverter Defibrillator (ICD) placement which led to right heart failure (RHF). His chief complaints were generalized fatigability and difficulty climbing steps at home. He also had orthopnea but denies paroxysmal nocturnal dyspnea. Despite using home diuretic regimen (Torsemide 40 gm daily), his continued to increase. He did not respond well to intravenous diuretics that time so decision was made to start Aquapheresis to which he responded very well Discussion: TV dysfunction associated with CIED leads can be investigated and diagnosed using different techniques. These pillars of diagnostic tests include two-dimensional (2D), 3D, and Doppler echocardiography. Presence of holosystolic hepatic vein flow reversal is key in diagnosing severe TR, whereas normal antegrade systolic flow excludes the possibility of moderate and severe TR. Conclusion: CIED leads causing tricuspid valve impairment has become increasingly recognized over the recent times; however, the evidence underlying this trend has been derived primarily from retrospective analyses. In order to circumvent these issues, leadless pacemakers and subcutaneous ICD devices should be considered. Highlights: CIED leads causing TV dysfunction has gained increasing recognition recently but all evidence supporting this premise emanates from retrospective analyses. When clinical, hemodynamic, and echocardiographic assessment provides compelling evidence of lead related severe TR, corrective intervention should be provided in a timely fashion, before the onset of severe annular and chamber dilation and severe RV dysfunction because, by that time, the lead itself will no longer be the problem, and the extant problem may not be as amenable to corrective intervention. Leadless pacemakers and subcutaneous ICD devices likely to be associated with a reduction in lead-related cardiac dysfunction.